PENGARUH BAHASA DAERAH (CIACIA) TERHADAP PERKEMBANGAN BAHASA INDONESIA ANAK USIA 2 SAMPAI 6 TAHUN DI DESA HOLIMOMBO JAYA - Maryam Nurlaila (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2016)
Abstract: Effect of Regional Languages (Ciacia) Indonesian Against Childhood Development 2 to 6 Years in Holimombo Jaya. This study aims to describe the influence of the local language (Ciacia) on the development of Indonesian children aged 2 to 6 years in Holimombo Desa Jaya. The method used in this research is descriptive qualitative method. Source of the data obtained from children aged 2 to 6 years in Holimombo Desa Jaya. To that end, have several informants, the one child who was 2 years old, one child is 3 years old, one child aged 5 years and one child aged 6 years. This research data is data in the form of orally-speech utterances of children. The technique used in this study is a recording technique and technical notes. Data processing begins with editing, classification, verification, and analysis. The research results show that the language in general, children in the village Holimombo Jaya is influenced by the local languages. The influence of the entry of the local language caused environmental factors and family environment where children were playing.